2014
DOI: 10.1002/gea.21483
|View full text |Cite
|
Sign up to set email alerts
|

The Berelekh Mammoth “Graveyard”: New Chronological and Stratigraphical Data from the 2009 Field Season

Abstract: To clarify unanswered questions of site formation, geology and the archaeology of the Berelekh geoarchaeological complex, a special survey was undertaken in 2009 of the area surrounding the site. Several geological units have been revealed. By establishing the spatial and temporal relationship of these deposits—as well as their age—we have reconstructed the formation history of the Berelekh bone bed. The mammoth bone deposit belongs to a paleochannel. Radiocarbon dating of mammoth remains at Berelekh demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…This industry conceivably represents the descendants of the standstill population spreading out of their postulated refugium in the central lowland after the LGM. New dates from a site near the mouth of the Indigirka River in northwestern Beringia ( Berelekh ) indicate the presence of people making teardrop‐shaped bifacial points (Chindadn points) and stemmed points at 14,900‐13,500 cal BP . As noted earlier, stemmed points are found in younger occupations at Ushki in central Kamchatka (∼13,000 cal BP), while Chindadn points are known from sites of comparable age (∼14,000‐13,300 cal BP) in south‐central Alaska and southwest Yukon …”
Section: Post‐lgm Beringia and Human Settlement Of The Americasmentioning
confidence: 78%
See 2 more Smart Citations
“…This industry conceivably represents the descendants of the standstill population spreading out of their postulated refugium in the central lowland after the LGM. New dates from a site near the mouth of the Indigirka River in northwestern Beringia ( Berelekh ) indicate the presence of people making teardrop‐shaped bifacial points (Chindadn points) and stemmed points at 14,900‐13,500 cal BP . As noted earlier, stemmed points are found in younger occupations at Ushki in central Kamchatka (∼13,000 cal BP), while Chindadn points are known from sites of comparable age (∼14,000‐13,300 cal BP) in south‐central Alaska and southwest Yukon …”
Section: Post‐lgm Beringia and Human Settlement Of The Americasmentioning
confidence: 78%
“…These initially were found in the Upper Tanana Valley in east‐central Alaska in association with microblades, but later were found in assemblages without microblades in the northern foothills of the Alaska Range . The dating of the oldest site in the Alaska Range is ∼13,500–13,000 cal BP, but a teardrop‐shaped point recently was recovered from northwestern Beringia dating to ∼14,900‐13,500 cal BP . The status of the teardrop‐shaped points and their relationship to the microblade industry has always been controversial, with some archeologists suggesting that the points actually are part of the microblade industry; that is, that they were made by the same people .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soffer et al, 2001;Niven, 2006), as has been suggested for P redmostí and Milovice (Musil, 1968;Brug ere and Fontana, 2009). For example, extensive geoarchaeological work has shown that the Berelekh mammoth bone bed, which Shipman has suggested may be an example of 'repeated, non-selective hunting' (page 3), actually consists of a series of natural deposits unrelated to the Berelekh archaeological site, though the human occupants later exploited the raw material as a resource (Pitulko, 2011; see also Pitulko et al, 2014).…”
Section: Taphonomic Considerationsmentioning
confidence: 97%
“…Alluvial sites are ideal for site preservation, providing valuable data for reconstructing site formation and archaeological context (Wriston, 2003;Hoffecker et al, 2014;Pitulko, Basilyan, & Pavlova, 2014). However, in the Intermountain West alluvial activity is usually marked by abrupt transitions from long-term dry conditions to high-energy flood events that carve out arroyos and erode cultural deposits (Waters, 1991) or form rapidly anastomosing braided systems, jumbling artifacts, as in the deepest layers of the Sunshine locality in Nevada where camel bones were redeposited with Paleoarchaic artifacts within gravelly channel deposits (Huckleberry, 2001;Beck & Jones, 2009).…”
Section: Introductionmentioning
confidence: 99%